MATERNAL KNOWLEDGE OF COMPLEMENTARY FEEDING, COMPLEMENTARY FEEDING INTAKE, AND HISTORY OF EARLY COMPLEMENTARY FEEDING INTAKE AMONG STUNTED AND NON-STUNTED CHILDREN AGED 12–24 MONTHS IN THE GANTING COMMUNITY HEALTH CENTER AREA, GEDANGAN DISTRICT, SIDOARJO - Zaqia Saila Safani; Amalia Ruhana (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Stunting remains a major nutritional problem in children under two years old (toddlers), and one factor suspected to play a role is the practice of providing complementary feeding intake to breast milk (MPASI). This study aims to analyze differences in maternal knowledge regarding MPASI, MPASI intake, and history of early MPASI provision in stunted and non-stunted children aged 12–23 months in the Ganting Community Health Center Working Area, Gedangan District, Sidoarjo Regency. The study used an observational analytical design with a matched case-control approach. The study population was toddlers aged 12–23 months and their mothers. The sample consisted of 60 mother-child pairs selected by purposive sampling: 30 stunted children as the case group and 30 non-stunted children as the control group, matched by age and gender. Data were collected using a MPASI knowledge questionnaire, interviews regarding the history of early MPASI provision, the 24-hour dietary recall method, and anthropometric measurements. Data analysis was performed using the McNemar test and Odds Ratio (OR) calculation. The results showed a significant difference in maternal knowledge regarding complementary feeding (p<0.001) and history of early complementary feeding (p=0.022), while complementary feeding intake based on the Minimum Acceptable Diet indicator did not show a significant difference (p=0.332). It was concluded that low maternal knowledge and a history of early complementary feeding were factors that differentiated the stunted and non-stunted groups, while complementary feeding intake did not show a significant difference